The impact of ademetionine and ipidacrine/phenibut on the NCAM distribution and behavior in the rat model of drug-induced liver injury - Muraviova, Diana; Kharchenko, Yuliia; Pierzynowska, Kateryna; Pierzynowski, Stefan Grzegorz; Wolinski, Jarek; Dyomshyna, Olga; Zhyliuk, Volodymyr; Ushakova, Galyna (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Recently, more attention is being paid to the drug-induced liver injury (DILI) as a consequence of the tuberculos is treatment and the need for new medicine is emphasized. The use of isoniazid and rifampicin has a potentiating effect, which increases the risk of substancial liver damage. In turn, systemic accumulation of toxic metabolites leads to negative changes in various organs, including the brain. It causes an imbalance in biochemical and neurophysiological processes in the brain, ultimately giving the onset to the development of hepatic encephalopathy. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The effects of rifampicin and isoniazid on the central nervous system have not been studied before and we aimed to evaluate the impact these two substances have on the neuronal cell adhesion molecules (NCAM) distribution and animal behavior in the rat model of DILI. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The 24 male Wistar rats, weighing 180-220 g were used for the experiment and divided to the groups (n=6): 1 – control; 2 – rats with experimental DILI; 3 – rats with DILI plus the intravenous infusion of S-adenosyl-L-methionine at a dose of 35 mg/kg; 4 – rats with DILI plus a fixed combination of ipidacrine hydrochloride at a dose 1 mg/kg body weight and phenibut at a dose 60 mg/kg body weight daily for the last 14 days of the experiment. All experimental procedures were carried out in the accordance with the principles outlined in the current Guide to the Care and Use of Experimental Animals. The locomotor and research activities were studied in the open field test. The activity of aspartate aminotransferase (AST, ЕС 2.6.1.1) and alanine aminotransferase (ALT, ЕС 2.6.1.2) in the serum of rats were tested to confirm the liver damage. The quantitative analyses of soluble and membrane forms of NCAM were performed with ELISA. The ANOVA followed by a Tukey post-hoc test was used to assess statistical differences between groups. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Our investigation in the open field test revealed a significant decrease in the locomotor and research activity of rats after 28 days of rifampicin and isoniazid administration. The recovery of investigated parameters was observed in groups of animals treated with ademetionine (AD group) or combination of ipidacrine and phenibut (IP/PB group). We also observed that changes in rats’ behavior were consistent with alterations of the NCAM levels in the thalamus and hippocampus. Thus, the level of membrane NCAM was significantly decreased under DILI in both investigated brain regions (thalamus and hippocampus), while both AD and IP/PB treatments restored membrane NCAM levels towards those observed in the control group at least in the hippocampus. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Obtained data suggests that both ademetionine and combinated drug containing ipidacrine and phenibut possesses neuroprotective properties and could prevent the decline in synaptic plasticity under antitubercular therapy.